“SONATA FOR CLARINET SOLO” BY TIBERIU OLAH - Răzvan METEA (Studia Universitatis Babeş-Bolyai. Musica)
. "A man of short stature, but with tremendous force of communicating by means of sounds; modest, but aware of his own value; secluded and slightly detached from the practical aspects of existence, but proving, in everything connected with the art of sounds, an inexhaustible energy and passion, an amazing capacity of observation and synthesis, unparalleled culture and memory as well as extraordinary precision and exigency. Apparently, Olah led an ordinary life, among us; in fact, music permeated his life as an uninterrupted ostinato, to the point of identification with it, in symbiotic communion. His personality takes prominent shape even from his first works: a strong lyrical nucleus, intense dramatism and contaminating kinetic energy " (Olguţa Lupu - March 2010[1]).